Estudo da 3-metilglutaconil coa hidratase da via de degradação de leucina de trypanosoma brucei - Stein, Mariana Leão de Lima [UNIFESP] (2016)
The parasite Trypanosoma brucei is the causative agent of African Trypanosomiasis. It is a flagellated protozoan parasite that develops into tsetse flies and blood and lymphatic systems of various mammals causing sleeping sickness in humans and Nagana in animals. The parasite acquires nutrients such as sugars, lipids and amino acids from their hosts. Amino acids are used to generate energy and also for protein and lipid synthesis. However, it is still unknown how T. brucei catabolize most of the amino acids, among them, the branched chain amino acids as leucine, isoleucine and valine. This thesis focused in understanding the role of the leucine degradation pathway in the T. brucei, as leucine is one of the precursors for the production of mevalonato and then to the synthesis of ergosterol, an essential steroid for the parasite. Therefore, we characterized the enzyme named 3-methylglutaconil-Coenzyme A hydratase (3-MGCoA-H), which transform 3-H-MGCoA into 3-hydroxymethylglutaryl coenzyme A (3-HMG), a substrate for the synthesis of mevalonate after the action of 3-hidroximetilglutaril CoA reductase (HMGR). Initially, we detected the gene and enzymatic activity of 3 H-MGCoA in the T. brucei. We found that it is a dimer, which localizes in the mitochondrial matrix and is expressed in both procyclic and bloodstream forms. The depletion of 3-MGCoA-H by RNA interference (RNAi) affected minimally the proliferation of parasite procyclic forms and has no effect on bloodstream forms. However, the addition of excess of leucine in the medium caused growth defects after RNAi induction in both parasite forms forms. This growth inhibition was reverted by addition of fetal bovine serum, but not by de-lipidated fetal bovine serum in bloodstream forms, suggesting that lipids can replace the deficiency generated by the lack of leucine catabolism. Furthermore, the mevalonate was able to restore the growth of procyclic forms. We then, analyzed the steroid content in the parasite after knockdown of the 3-MGCoA-H in different concentrations of leucine. We detected that knockdown parasites growth with an excess of leucine, showed lower amounts of lipid droplets, reduced levels of ergosterol in relation to cholesterol, which is normally scavenged from the serum by the parasite. These results suggest that the downregulation of leucine catabolism affects the mevalonate pathway and consequently, the ergosterol biosynthesis. This could occur by the accumulation of leucine catabolites complexed with CoA, affecting the CoA pool, or directly by direct inhibition of specific enzmes such as the HMGR. These effects could explain why humans with 3-methylglutaconic aciduria type I due to mutations in the 3-MGCoA-H exhibit neurological deficits.